Internalisasi nilai melalui penerapan strategi modelling dalam pembelajaran Pendidikan Agama Islam di sekolah dasar - Kholidah, Lilik Nur (S1 Pendidikan Sekolah Dasar UPP III FIP, Universitas Negeri Malang, 2012)
Abstract: Elementary School which is a continuation of kindergarten education occupies an important position in the formation of individual personality. At this level of education, the basic of personality formation is laid out. when students obtain an optimal coaching, its will greatly affect the pattern of his life in the future. For this age level modeling strategy is effective in shaping children's personality. The implementation of modeling method will help the internalization of a variety moral behavior, pro social and other social rules. Key Word: Value Internalization, Islamic Religious Education, Modelling Method